2011
DOI: 10.1558/genl.v5i1.89
|View full text |Cite
|
Sign up to set email alerts
|

'Snippa'

Abstract: Second wave feminist linguistics has investigated sexist language practices. In Sweden it has often been claimed there is no neutral word for girls’ genitals. The article describes a feminist language reform aimed at establishing the word snippa as a neutral word for the female genitals. Snippa now seems to be one of the most common words to denote girls’ genitals, is included in dictionaries and used in printed books. The article discusses what made this reform successful and also considers whether the word i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Another example of the micro politics of choosing particular words concerned the urgency of finding suitable words for female genitalia, a question which has been stressed in several contexts over the years (Milles 2011). The problem that was firmly addressed was primarily the risk of mystifying or reproducing an inability to speak about female genitals at all.…”
Section: Careful Choice Of Wordsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of the micro politics of choosing particular words concerned the urgency of finding suitable words for female genitalia, a question which has been stressed in several contexts over the years (Milles 2011). The problem that was firmly addressed was primarily the risk of mystifying or reproducing an inability to speak about female genitals at all.…”
Section: Careful Choice Of Wordsmentioning
confidence: 99%
“…The problem that was firmly addressed was primarily the risk of mystifying or reproducing an inability to speak about female genitals at all. In classes, we noted a variety of terms such as 'vagina', mutta (the latter translates into cunt or pussy) and snippa, a term launched by feminist sex educators in the early 2000s, now widely spread and accepted as a neutral and colloquial name for the female genitals, as a counterpart to the male snopp ('willy') (Milles 2011, see also Sherlock 2015). In the education classes these terms were used synonymously, though it was suggested that some were more appropriate when visiting a pharmacy and others when speaking among friends and partners.…”
Section: Careful Choice Of Wordsmentioning
confidence: 99%
“…Roberts and Sarangi 2003). Increasingly, direct problem-solving using this approach is happening in various applied linguistic fields such as second language learning (Burns 2010); feminist language planning (Milles 2011); health settings (Roberts 2003); speech and language therapy (e.g. Litosseliti and Leadbetter 2013); forensic linguistics (e.g.…”
Section: Problem-solving Research In the Field Of Workplace Discoursementioning
confidence: 99%
“…Burns, 2010), feminist language planning (e.g. Milles, 2011), health settings (e.g. Roberts, 2003), speech and language therapy (e.g.…”
Section: Introductionmentioning
confidence: 99%